Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

[Letter to M. Sebastien Proulx, Minister of Education] - Lemay, Diane (2017)

[Lettre à M. Sébastien Proulx Ministre de l’Éducation] - Lemay, Diane (2017)

[Letter for St Gabriel School] - McDaid, Mary (2011)

[La religion en éducation pour les enfants] - McDaid, Mary (2011)

[Religion in Early Childhood Education Facilities and Daycare] - McDaid, Mary (2011)

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.